2020
DOI: 10.1039/d0ma00231c
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase-like behavior and photothermal effect of chitosan-coated Prussian-blue nanoparticles: dual-modality antibacterial action with enhanced bioaffinity

Abstract: Mechanism of peroxidase-like activity and photothermal effect of chitosan-coated Prussian blue nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…75 The above discussed heteroatoms have their own unique properties, but out of all of these, nitrogen is best because of its half shell electronic configuration and presence of a lone pair. 23,[76][77][78][79][80][81][82] The comparable atomic size of nitrogen and carbon makes it highly suitable for doping in the carbon framework. 83 These lone pairs act as electron donor sites, which make them an active site for substrate catalysis and provide a path with low activation energy.…”
Section: Effect Of Heteroatom Incorporationmentioning
confidence: 99%
“…75 The above discussed heteroatoms have their own unique properties, but out of all of these, nitrogen is best because of its half shell electronic configuration and presence of a lone pair. 23,[76][77][78][79][80][81][82] The comparable atomic size of nitrogen and carbon makes it highly suitable for doping in the carbon framework. 83 These lone pairs act as electron donor sites, which make them an active site for substrate catalysis and provide a path with low activation energy.…”
Section: Effect Of Heteroatom Incorporationmentioning
confidence: 99%
“…However, as PB nanocrystals generate heating upon exposure to visible light, their antibacterial activity can be significantly enhanced upon combined photothermal therapy. We have demonstrated that the antibacterial action of the PB nanocrystal platform can be further enhanced upon coating with a layer of chitosan that facilitates high affinity electrostatic interaction with both Gram-positive and Gram-negative bacterial cells [ 52 ]. In a separate work, we have shown that upon doping silver ions in the PB network, very high broad-spectrum antibacterial action could be observed due to the combined effects of ROS generation and silver-ion-mediated toxicity, along with a photothermal effect [ 53 ].…”
Section: Nanozyme Platforms For Antibacterial Applicationsmentioning
confidence: 99%
“…For example, since iron-oxide-based nanoparticles have already been used as clinical MR contrast agents, iron-oxide -based nanozymes can be considered as promising candidates in this regard. On the other hand, Prussian blue (PB) nanoparticles are used clinically for the removal of radioactive contaminants in humans [ 52 , 53 ]; thus, PB-based nanozymes can also be explored for advanced clinical aspects. Other nanozymes based on biocompatible nanoparticles, such as graphene oxide, metal–organic frameworks, single-atom nanozymes, etc., are also being extensively explored in this regard.…”
Section: Challenges and Opportunities Of Nanozymesmentioning
confidence: 99%
“…Roy and colleagues have found that the well-known pigment Prussian Blue (PB), and its analogues (PBAs) can serve as efficient nanoparticulate photothermal agents [200]. They have demonstrated efficient bactericidal and anticancer action using a formulation of chitosan-coated PB nanoparticles irradiated with red-emitting laser light [201]. Recently, it has been recognized that localized PTT also triggers a systemic immunogenic response that affects cancer cells in non-target regions (abscopal effect) [192,202].…”
Section: Photothermal Therapymentioning
confidence: 99%